2018
DOI: 10.1590/1678-4685-gmb-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

The UCP2 -866G/A, Ala55Val and UCP3 -55C/T polymorphisms are associated with premature coronary artery disease and cardiovascular risk factors in Mexican population

Abstract: We examined the role of UCP gene polymorphisms as susceptibility markers for premature coronary artery disease (pCAD). The UCP2 Ala55Val (C/T rs660339), UCP2 -866G/A (rs659366), and UCP3 -55C/T (rs1800849) polymorphisms were genotyped in 948 patients with pCAD, and 763 controls. The distribution of the UCP2 A55V (C/T rs660339) and UCP3 -55 (rs1800849) was similar in patients and controls. However, under a recessive model, the UCP2 -866 (rs659366) A allele was associated with increased risk of developing pCAD (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
4
0
1
Order By: Relevance
“…AA genotype carriers who survived ischemic stroke showed a higher functional status as compared with GG and GA genotype carriers (Díaz-Maroto Cicuéndez et al 2017). At the same time, the A allele increased the risk of developing coronary artery disease in the Mexican population (Gamboa et al 2018) and in males of the European population (Dhamrait et al 2004). The Ala55Val polymorphism is in Ucp2 exon 4, where a C/ T nucleotide substitution leads to a substitution of alanine for valine at position 55 of the UCP2 amino acid sequence (Fig.…”
Section: G-866a Polymorphism Of the Ucp2 Genementioning
confidence: 96%
“…AA genotype carriers who survived ischemic stroke showed a higher functional status as compared with GG and GA genotype carriers (Díaz-Maroto Cicuéndez et al 2017). At the same time, the A allele increased the risk of developing coronary artery disease in the Mexican population (Gamboa et al 2018) and in males of the European population (Dhamrait et al 2004). The Ala55Val polymorphism is in Ucp2 exon 4, where a C/ T nucleotide substitution leads to a substitution of alanine for valine at position 55 of the UCP2 amino acid sequence (Fig.…”
Section: G-866a Polymorphism Of the Ucp2 Genementioning
confidence: 96%
“…One of the most reported UCP2 variant is the missense variant rs660339 in exon 4, a C to T transition, resulting in an amino acid substitution at position 55 of the UCP2 (Ala55Val) which seems to modify the uncoupling degree and consequently protein activity ( 72 ). In particular, the Val/Val genotype has been associated with lower degree of uncoupling, increased metabolic efficiency, lesser fat oxidation, reduced energy expenditure, higher exercise efficiency, higher risk of obesity and diabetes, elevated atherogenic index, and greater weight loss compared to the Ala/Val and Ala/Ala genotypes ( 77 , 78 ). UCP2 demonstrates tissue specific physiological effects as suggested by its tissue-specific regulation e.g., in the brain UCP2 functions as a regulator of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, some evidence has suggested that the mutations of UCP2 genes can affect the activity or expression levels of UCP2 by increasing the coupling of oxidative phosphorylation, which might cause the reduction of energy expenditure and subsequently contribute to the development of obesity and diabetes 14 . At present, most previous studies have found that two common polymorphisms of UCP2 gene including rs659366 (located in the promoter region) and rs660339 (a missense variant in exon 4) were closely associated with obesity and diabetes 12 , 31 , 32 . Furthermore, maternal obesity and diabetes have been identified as risk factors of CHDs, which indirectly indicated that genetic variants of UCP2 may be associated with the risk of CHDs in offspring.…”
Section: Discussionmentioning
confidence: 99%